Respon Fisiologis Ayam KUB dari Penambahan Probiotik Rayakemo dalam Air Minum: Physiological Response of KUB Chickens from the Addition of Rayakemo Probiotics to Drinking Water - Siregar, Rahmat Martua; Sari, Devi Kumala; Fati, Nelzi (Fakultas Peternakan Universitas Jambi, 2024)
Background: Rayakemo probiotics (tape yeast, yakult, old coconut water and molasses) contain beneficial microorganisms such as Lactobacillus casei and Saccharomyces which can provide health benefits to the host. Purpose: This study aims to determine the effect of adding Rayakemo probiotics to drinking water on the weight percentage of the spleen, liver, heart, small intestine and length of the small intestine of KUB chickens. Method: This research was carried out for two months, from March to May, in the Payakumbuh State Agricultural Polytechnic chicken coop. A total of 100 KUB chickens were used without separating gender and randomly divided into 20 experimental units, with each unit consisting of 5 KUB chickens. The chickens were kept for 8 weeks and data was collected in the 8th week at harvest. The method used in this research was the RAL method (Completely Randomized Design) with 4 treatments and 5 replications. Each treatment is: A: drinking water without Rayakemo probiotics, B: 3% Rayakemo probiotics + drinking water, C: 6% Rayakemo probiotics + drinking water and D: 9% Rayakemo probiotics + drinking water. Results: The results showed that the addition of Rayakemo probiotics to drinking water on the weight percentage of spleen, liver, heart, small intestine and small intestine length of KUB chickens had no significant effect (P>0.05). Conclusion: The addition of Rayakemo probiotics in drinking water did not significantly affect the spleen, liver, heart, small intestine weight and small intestine length. The addition of Rayakemo probiotics in drinking water up to 9% can be tolerated by broilers against the spleen, liver, heart, small intestine weight and small intestine length.